Геоинформационно-картографические технологии историко-географических исследований западного региона Украины - Ковальчук, Іван Платонович; Kovalchuk, Ivan P.; Андрійчук, Юрій Михайлович; Andriichuk, Yurii M; Швець, Оксана Іванівна; Shvets, Oksana I.; Жданюк, Богдан Степанович; Zhdaniuk, Bohdan S. (Русское географическое общество, 2013)
В статті розглядаються ГІС-технології для вирішення проблем,які виникають в процесі регіонального історичного та географічного аналізу. Стаття реконструює історію розвитку довкілля в регіоні, оцінює структурні зміни в компонентах навколишнього середовища, і ідентифікує основні зміни. The present article discusses the GIS technologies to address problems in the process of regional historical and geographical analysis. By applying them the directions and intensity of development of transformational processes in geosystems of Western Ukraine were identified. The article reconstructs the history of environmental development in the region, assesses structural changes in environmental components, and identifies major variables thereof.
The geoinformational-cartographic technologies in historical-geographic research of west Ukraine region
Keywords: ГИС технологии; западные регионы Украины; ГІС технології; західні регіони України